Frank Capra's you can't take it with you [videorecording (DVD)] - Riskin, Robert; Capra, Frank, 1897-1991; Arthur, Jean, 1900-1991; Barrymore, Lionel, 1878-1954; Stewart, James, 1908-1997; Arnold, Edward, 1890-1956; Auer, Mischa, 1905-1967; Miller, Ann, 1923-2004; Byington, Spring, 1886-1971; Hinds, Samuel S., 1875-1948; Meek, Donald, 1878-1946; Warner, H. B. (Henry Byron), 1876-1958; et al. (Columbia Pictures : Sony Pictures Home Entertainment, 2008)
When the stenographer from an eccentric family falls in love with the son of a rich mogul, the two families clash. Their love will change everything.